2015
DOI: 10.1111/papr.12309
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Sham‐Controlled Acupuncture in Experimental Visceral Pain – a Randomized, Single‐Blinded Study

Abstract: The presented sham procedure provides a valid method for blinding of "sham acupuncture" and may be used in future blinded controlled trials of acupuncture for visceral pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Two studies included irritable bowel syndrome (IBS) patients [15, 16], and one study involved primary dysmenorrhea [17] and another study involved chronic pancreatitis patients [18]. Further, a study by Kotani et al [19] investigated postoperative visceral pain in patients who underwent upper or lower abdominal surgeries [18], and two studies involved healthy participants [20, 21] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies included irritable bowel syndrome (IBS) patients [15, 16], and one study involved primary dysmenorrhea [17] and another study involved chronic pancreatitis patients [18]. Further, a study by Kotani et al [19] investigated postoperative visceral pain in patients who underwent upper or lower abdominal surgeries [18], and two studies involved healthy participants [20, 21] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Among the seven studies conducted on humans, the various types of acupuncture techniques that were used are as follows: MA in four studies [17–19, 21], acu-TENS in three studies [16, 17, 20], and EA in two studies [15, 17]. Most of these studies described the stimulation method that was used, the intensity (frequency, voltage, and amperage), and the locations of acupoints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the blunt tip of the needle reaches the skin, the needle body is pushed into a hollow needle handle, hence blinding the patient but not the practitioner . Furthermore, the structure of single‐blind sham needle used in Juel's study , which has been cited by Choi and Lam , is different from the Streitberger and Park needles, and thus the sharp tip of a hollow inner tube provides patients with a pricking sensation .…”
mentioning
confidence: 99%
“…Placebo acupuncture needles are metallic retractable needles with blunt tips which can prick the skin, but are fitted with a stopper that prevents the needle from advancing further when it has reached the specified position. Therefore, the needle is not actually inserted into the flesh . Reports of the success of blinding using retractable acupuncture needles vary , but most well‐controlled studies have found them to be inadequate in blinding either the acupuncturist or the subjects, with up to 83% of acupuncturists and 68% of subjects correctly identifying which needles were being used .…”
mentioning
confidence: 99%